Exploring Work System Adaptations in Providing Care for Children with Medical Complexity in the Home. (December 2020) - Barton, Hanna J.; Loganathar, Shanmugapriya; Singhe, Nawang; Ehlenbach, Mary L.; Katz, Barbara; Coller, Ryan J.; Werner, Nicole E.
Children with medical complexity (CMC) rely on family caregivers to provide advanced medical care in the home. Yet, family caregivers are often under-supported. To better support family caregivers, we must understand and identify the ways that the work system is not designed to support their work. Work system adaptations can uncover where the work system is not designed to support the worker. This study sought to identify and categorize caregiver adaptations to the work system. We conducted 30 home-visit interviews with caregivers of CMC. Inductive content analysis revealed that family caregivers were making work system adaptations on multiple levels including: medical devices, direct care, auxiliary care, and integration of caregiving into everyday life. Our findings imply that family caregivers are attempting to address barriers on multiple levels by adapting the work system. Critical next steps should create system interventions to address the mismatch between the caregivers' needs and the work system.